Ação do hormônio triodotironina (T3) altera a expressão gênica do oncogene Amphiregulin (Areg) el células tumorais de adenocarcinoma de mama - Sibio, Maria Teresa De [UNESP] (2014)
The incidence of breast cancer (BC) has increased alarmingly in recent years. Several studies have been lead to the discovery of amphiregulin (AREG) as an oncogene, with its expression related to various cancer types. Our group showed the action of T3 on different genes in BC cells using microarray, but the mechanism which T3 regulates the expression of these genes and the involvement of ER have not been evaluated yet. The relationship between the expression of AREG and the presence of TH remains unknown, therefore, the aim of this study was to verify the nuclear and extra-nuclear action of T3 on AREG gene expression in breast adenocarcinoma cell lines, MCF-7 and MDA-MB-231. The cell lines were subjected to treatment with 10-8M T3 at the times 10', 30', 1h and 4h in the presence or the absence of Fulvestrant (ICI 182,780) - ER inhibitor, Actinomycin D (ACTD) - inhibitor of gene expression, cycloheximide (CHX) - inhibitor of protein synthesis, and LY294002 - inhibitor of PI3K pathway. The AREG mRNA levels were analyzed by RT-PCR. For data analysis we used ANOVA followed by the post hoc Tukey's test with a significance level of 5%. T3 increased AREG gene expression levels, compared to the control group in both cell lines, regardless of the incubation times. Our study confirms that AREG gene expression is increased in the presence of T3 in both cell lines and at all the times studied. The data from this study indicate that T3 might act through ER, decreasing AREG expression after 30' treatment in MCF-7 cells and did not alter the expression of this gene in MDA-MB-231 cells, which lack ER. Furthermore, we suggest that T3actionon AREG gene expression occurs indirectly. The T3 maintains AREG expression even after the inhibition of transcription. And, the PI3K pathway activation by T3 is required for the modulation of AREG in both cell lines studied